The Effect of Health Education on the Knowledge and Attitude of Brides and Grooms in the Community Health Center of Duri Pulo Village Gambir Sub-District in 2020 - Rizqah, Miftah; Widowati, Retno; Indrayani, Triana (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This study aims to identify the effect of health education on the knowledge and attitude of brides and grooms in the community health center of Duri Pulo Village Gambir Sub-District. This was a quasi-experimental study with one-group pre-posttest design. The results showed that the mean values of pretest and posttest were 1.75 and 3.05, respectively, showing 1.3 difference between the two. The p value was 0.00, meaning that the p value <0.05, hence, Ho was rejected. There was an effect of health education on the knowledge and attitude of brides and grooms. For the health center in question, the researcher is expected to hold a health outreach or education on the knowledge and attitude of brides and grooms